2019
DOI: 10.1021/acs.jpcc.9b06790
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Néel and Brownian Relaxations Isolated from Complex Dynamics Influenced by Dipole Interactions in Magnetic Nanoparticles

Abstract: The magnetization dynamics involved in applying an alternating field are composed of a superposition of Neél and Brownian relaxations. To evaluate the mechanisms of magnetic relaxations, it is necessary to individually evaluate the Neél and Brownian regimes. In this study, by applying a fast responding pulse field, the two-step magnetization response of magnetic nanoparticles dispersed in a fluid in the Brownian regime occurred after the Neél regime. We isolated Neél and Brownian relaxations from an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 57 publications
(99 reference statements)
5
71
0
1
Order By: Relevance
“…11 In another set of very recent experiments, the concentration dependence of the magnetization relaxation has been measured and the Brownian and Néel contributions have been identified. 7 While the effective Brownian relaxation time was found to increase with increasing concentration, a weaker, opposite behavior was observed for the effective Néel relaxation time. Furthermore, the corresponding dynamic magnetic susceptibility deviates strongly from the Debye law for noninteracting MNPs and the effective relaxation time (1) is not sufficient to describe the behavior.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…11 In another set of very recent experiments, the concentration dependence of the magnetization relaxation has been measured and the Brownian and Néel contributions have been identified. 7 While the effective Brownian relaxation time was found to increase with increasing concentration, a weaker, opposite behavior was observed for the effective Néel relaxation time. Furthermore, the corresponding dynamic magnetic susceptibility deviates strongly from the Debye law for noninteracting MNPs and the effective relaxation time (1) is not sufficient to describe the behavior.…”
Section: Introductionmentioning
confidence: 93%
“…with transition rates w. Equations of the type (5) with (6) and (7) are known in the literature as ''differential Chapman-Kolmogorov'' equations. 33 In order to complete the model, we therefore need to specify the transition rates w in eqn (7). We here follow ref.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 64,66 ] In this linear approximation, the hysteresis loop area is given by A=πμ0Hnormalac2VnormalmMnormals23knormalBT2πfτ[]1+2πfτ2where μ 0 is the permeability of free space (4π × 10 −7 m kg s −2 A −2 ), M s is the saturation magnetization, V m is the volume of the particles, k B is the Boltzmann constant (1.38 × 10 −23 J K −1 ), T the absolute temperature (in Kelvin) and τ is the Néel–Brown relaxation time. [ 67 ] The Brownian ( τ B ) and Néel ( τ N ) relaxation times of a single superparamagnetic nanoparticle assuming as sphere can be calculated utilizing the following formulas τnormalN=τ0expKeffπDm36kBT τB=πηDh32kBTWhere τ N is the Néel relaxation time, τ 0 is the effective relaxation time (≈10 −9 s), K eff is the magnetic anisotropy constant, D m is the magnetic core diameter from TEM, k B is the Boltzmann constant (1.38 × 10 −23 J K −1 ), T is the absolute temperature in Kelvin, τ B is the Brownian relaxation time, η is the dynamic viscosity of the surrounding medium ( η is the 0.7978 × 10 −3 kg m −1 s −1 for water) and D h is the hydrodynamic diameter (the diameter of the particle plus adsorbed surfactant, derived from dynamic light scattering (DLS)). [ 19f ] Considering that these two independently mechanisms take place simultaneously, the effective relaxation time τ eff is given by τnormaleff=τNτBτN+τBwhen τ N ≫ τ B or τ N ≪ τ B , the dominant mechanism as described by τ eff , is determined by the shorter of the two relaxation times.…”
Section: Physical Modeling Of Magnetic Heating and Cell Death Pathwaysmentioning
confidence: 99%
“…This effect was mainly due to the higher operating frequency of the thermometric setup (100 kHz) with respect to the B-H loop tracer (69 kHz) and it also included the contribution to the SLP of the Brown relaxation process that took place only in the magnetic liquid solution and not in the dried sample used for dynamic hysteresis loops measurements [24,87]. In fact, the Brown relaxation mechanism is associated with the physical rotation of the whole particle in the fluid generating heat due to the viscous friction between the rotating particles and the surrounding liquid medium [24,87,88]. However, recent studies, both in vivo and ex vivo, have demonstrated that the particles are generally immobilized when directly injected into the tumor tissues highlighting that the Brown process is largely suppressed during hyperthermia treatments [89][90][91].…”
mentioning
confidence: 99%